A Reverse-Engineered Pitch on The Scorching Truth: Investigating the Impact of Heatwaves on Selangor's Elderly Hospitalizations - Yen Nee Teo; Kun Hing Yong (Journal of Accounting and Management Information Systems (JAMIS), 2023)
The pitch template introduced by Faff (2015; 2021) has become increasingly popular in academic research. Therefore, this paper aims to offer readers new ideas about a more time-efficient and easy-to-understand way of exploring a new research area and topic through a reverse engineering approach. The author believes that a reverse engineering pitch is the cornerstone to assist new researchers or PhD students to sharpen their pitching skills before they start to prepare an original pitch for a new research topic.
Keywords: I15; I18; 650; Reverse engineering; pitching research; climate change; heatwaves; the elderly; hospitalizations; risk